Pemanfaatan Sistem Informasi Geografis dalam Mempercepat Penyediaan Informasi Ketersediaan Darah bagi pasien yang membutuhkan transfusi darah Untuk Mendukung Smart City - Mutia Fadhila Putri; Indra Maulana; Andini Dwi Lestari; Ermatita Ermatita (Annual Research Seminar (ARS), 2016)
The choosenmethod for this program are Requirement Analysis, Conceptual Modeling, Implementation and testing. This method is the one of development method of software engineering so that produced an application that could solve the problem by providing a softwre that integrates blood stock information across PMI and hospitals branches in all over Indonesia. This information system integrates blood stock information across PMI branchesandhospitals all over Indonesia, providing access to real time blood stock updates to people, providing information about PMI branchesandhospitals locations across Indon